2012
DOI: 10.2527/jas.2012-4242
|View full text |Cite
|
Sign up to set email alerts
|

Response of the modern lactating sow and progeny to source and level of supplemental dietary fat during high ambient temperatures

Abstract: The objective of this study was to determine the response to increments of 2 sources of dietary fat on lactating sow and progeny performance during high ambient temperatures. Data were collected from 391 sows (PIC Camborough) from June to September in a 2,600-sow commercial unit in Oklahoma. Sows were randomly assigned to a 2 × 3 factorial arrangement of treatments and a control diet. Factors included 1) fat sources, animal-vegetable blend (A-V) and choice white grease (CWG), and 2) fat levels (2%, 4%, and 6%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 78 publications
4
9
0
1
Order By: Relevance
“…The improvement in litter growth rate for sows fed supplemental fat at more than 5% had been observed previously (Shurson & Irvin 1992;Tilton et al 1999;Gatlin et al 2002;Lauridsen & Danielsen 2004) and only a few other studies have reported a significant positive effect on breast-feeding performance, by addition of fat less than 5% (except FO) (Neal et al 1999;Rosero et al 2012). The improvement in litter growth rate for sows fed supplemental fat at more than 5% had been observed previously (Shurson & Irvin 1992;Tilton et al 1999;Gatlin et al 2002;Lauridsen & Danielsen 2004) and only a few other studies have reported a significant positive effect on breast-feeding performance, by addition of fat less than 5% (except FO) (Neal et al 1999;Rosero et al 2012).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The improvement in litter growth rate for sows fed supplemental fat at more than 5% had been observed previously (Shurson & Irvin 1992;Tilton et al 1999;Gatlin et al 2002;Lauridsen & Danielsen 2004) and only a few other studies have reported a significant positive effect on breast-feeding performance, by addition of fat less than 5% (except FO) (Neal et al 1999;Rosero et al 2012). The improvement in litter growth rate for sows fed supplemental fat at more than 5% had been observed previously (Shurson & Irvin 1992;Tilton et al 1999;Gatlin et al 2002;Lauridsen & Danielsen 2004) and only a few other studies have reported a significant positive effect on breast-feeding performance, by addition of fat less than 5% (except FO) (Neal et al 1999;Rosero et al 2012).…”
Section: Discussionsupporting
confidence: 59%
“…In the present study, piglets from sows fed the FOor SO-supplemented diets had higher litter weaning weight, weaning survival rate and overall litter weight gain than piglets from sows fed the control diet. The improvement in litter growth rate for sows fed supplemental fat at more than 5% had been observed previously (Shurson & Irvin 1992;Tilton et al 1999;Gatlin et al 2002;Lauridsen & Danielsen 2004) and only a few other studies have reported a significant positive effect on breast-feeding performance, by addition of fat less than 5% (except FO) (Neal et al 1999;Rosero et al 2012). As an efficient vehicle transferring nutrient from the mother to the newborn, milk fat plays a major role in the supply of energy and in glucose homeostasis of newborn pigs (Sarkar et al 1985).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In the present study, the addition of 3,400 kcal/kg metabolizable energy (ME) increased piglet performances. Increasing the energy levels with additional fats or oils in diets is known as a nutritional strategy to support lactating sow exposed to heat stress [19,20], particularly in prolific lactating sows [9]. The increase in supplementation of fat and oil in lactation diets from 2% to 11% enhanced the energy intake of around 1,100 kcal ME per day [21].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing energy density with fats or oils is a nutritional strategy that seems to be particularly important for lactating sows under heat stress conditions (Rosero et al, 2012) and for prolific and high-producing lactating sows (Strathe et al, 2017a). In a literature review, the addition of 2% to 11% fats and oils in lactation diets improved the energy intake of sows by an average of 7% or 4.6 MJ ME per day (Rosero et al, 2016).…”
Section: Energy Requirements In Lactationmentioning
confidence: 99%